Psychosocial Interventions for Elderly People with Bipolar Disorder: Systematic Review with Meta-Analysis - Carolina Raquel Sales Vieira; Eduarda Rezende Freitas (Paidéia (Ribeirão Preto))
Abstract: Bipolar Affective Disorder is a chronic mental disorder that can have profound consequences for elderly people. The objective of this study was to analyse the evidence of the effectiveness of psychosocial and Cognitive-Behavioral Therapy-based interventions for bipolar disorder. To this end, a systematic review with meta-analysis was conducted based on randomized controlled trial, published between 2012 and 2022, that included elderly people in their samples. The search, carried out in the PubMed, SciELO, CENTRAL, and PePSIC databases, resulted in 1069 articles, 15 of which were included in this research. The recommendations of PRISMA and JBI were used. It was found that psychoeducation and, especially, interventions in Cognitive-Behavioral Therapy can improve symptoms of this disorder. Through meta-analysis, an effect in favour of Cognitive-Behavioral Therapy was observed for reducing mania, but not for depression. However, more studies are needed, as none conducted exclusively with elderly people were found.